2022
DOI: 10.3758/s13428-021-01770-8
|View full text |Cite
|
Sign up to set email alerts
|

Lying on the Dissection Table: Anatomizing Faked Responses

Abstract: Research has shown that even experts cannot detect faking above chance, but recent studies have suggested that machine learning may help in this endeavor. However, faking differs between faking conditions, previous efforts have not taken these differences into account, and faking indices have yet to be integrated into such approaches. We reanalyzed seven data sets (N = 1,039) with various faking conditions (high and low scores, different constructs, naïve and informed faking, faking with and without practice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…Although a detailed and complete list of them is beyond the scope of this article, in the following, we will nevertheless provide an overview of the most prominent traces that have been used in faking research along with prominent approaches in faking detection. So far, none of these procedures have been widely accepted ( Röhner et al, 2022 ). Also, none of them work without misclassification, which indicates that there are still factors that are not understood in the detection of faking.…”
Section: Traces Of Faking and Faking Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a detailed and complete list of them is beyond the scope of this article, in the following, we will nevertheless provide an overview of the most prominent traces that have been used in faking research along with prominent approaches in faking detection. So far, none of these procedures have been widely accepted ( Röhner et al, 2022 ). Also, none of them work without misclassification, which indicates that there are still factors that are not understood in the detection of faking.…”
Section: Traces Of Faking and Faking Detectionmentioning
confidence: 99%
“…This phenomenon is called intermittent faking ( Brown & Böckenholt, 2022 ). In this line of thinking, recent studies have demonstrated that test scores are not able to capture the complete picture of faking (e.g., Calanna et al, 2020 ; Röhner et al, 2022 ). Relatedly, studies have shown that looking at individuals’ responses to each individual item on the to-be-faked measure (in its entirety called individuals’ response patterns ; e.g., Calanna et al, 2020 ) may offer better insights into faking because individual items include information about traces of faking that are washed out in test scores (e.g., Böckenholt, 2013 , 2017 ; Calanna et al, 2020 ; Lee et al, 2022 ; Röhner et al, 2022 ; Sun et al, 2022 ).…”
Section: Traces Of Faking and Faking Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these claims, the definition of IATs (Greenwald & Banaji, 1995) should probably be reworked. Similarly, the claim that IAT effects result from uncontrollable processes (for an introduction, see De Houwer, 2006) has been empirically disproved by research showing that participants can fake on IATs (e.g., Röhner et al, 2022). This lack of clarity about what is implicit in IATs can be viewed as the first disease that has contributed to the death of IATs.…”
Section: What Killed Iats? Potentially Lethal Diseases Of Iatsmentioning
confidence: 99%
“…With respect to the fakeability of IATs, researchers have developed several faking indices (e.g., Röhner et al, 2023). However, research using machine learning demonstrated that faking indices were outperformed by processes such as participants’ speed-accuracy tradeoff that were disentangled with diffusion models to detect faking (Röhner et al, 2022). These results reflect theory and earlier empirical findings on faking in IATs that have been revealed to involve deliberately adapting speed and accuracy (e.g., Röhner et al., 2013).…”
Section: Attempts To Resurrect Iatsmentioning
confidence: 99%